A NEW METHODOLOGICAL APPROACH APPLIED IN THE 8TH GRADE VISUAL ARTS EDUCATION PROCESS: MULTIPLE INTELLIGENCE THEORY - KARAGÖZ, Tuğrul; OKUR, Ayşe (Atlas Journal, 2021)
The purpose of this research; To determine the effect of activities based on multiple intelligence fields applied in secondary school eighth grade visual arts education on students' success, attitude and permanence. Experimental research pattern was used in the study. The study group of the study was determined as the 8-C (29) and 8-E (29) study group from the 8th grade branches of Martyr Teacher Hüseyin Aydemir Hürriyet Secondary School in Mucur District of Kırşehir province in the 2018-2019 academic year. During the four-week implementation period, the lessons were carried out with the activity of the field of learning visual arts culture ‘If You Were You, How Would You Do It”. In accordance with this purpose; At the end of the 2-hour theoretical lesson, they applied 6 hours of practice to the experimental group in which the field activities were conducted. With the control group, the traditional curriculum was applied to the learning area. Achievement test was used as a data collection tool to measure the effect of students on achievement. Attitude test was used to determine the affective behaviors of students towards visual arts education practice. A retention test was applied to determine the permanence of the learned information. The data obtained in the study were analyzed with the t-test in SPSS 17 package program. In the statistical analysis made as a result of the research; It was observed that the attitude, achievement, and permanence scores of the experimental group in which the instruction based on Multiple Intelligence Theory was applied were higher than the control group.